2022
DOI: 10.1097/tp.0000000000004245
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Fibroblastic Reticular Cells Attenuate Immune Responses Through Induction of Tolerogenic Macrophages at Early Stage of Transplantation

Abstract: Background. Fibroblastic reticular cells (FRCs) are a type of stromal cells located in the T zone in secondary lymphoid organs. Previous studies showed that FRCs possess the potential to promote myeloid differentiation. We aim to investigate whether FRCs in lymph nodes (LNs) could induce tolerogenic macrophage generation and further influence T-cell immunity at an early stage of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods. LNs were assayed to confirm the existence of proliferating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…These findings are consistent with previous studies conducted to define ex vivo-generated regulatory macrophages. 6 Liu et al 5 This study has revealed a novel mechanism underpinning the role of the microenvironment in secondary lymphoid organs, specifically highlighting the interactions between FRCs and macrophages for immune tolerogenic regulation. Various aspects of lymph node FRCs and their role in inducing regulatory macrophages to treat or prevent GvHD remains to be fully elucidated.…”
Section: The Potential Clinical Application Of Induced Tolerogenic Ma...mentioning
confidence: 90%
See 4 more Smart Citations
“…These findings are consistent with previous studies conducted to define ex vivo-generated regulatory macrophages. 6 Liu et al 5 This study has revealed a novel mechanism underpinning the role of the microenvironment in secondary lymphoid organs, specifically highlighting the interactions between FRCs and macrophages for immune tolerogenic regulation. Various aspects of lymph node FRCs and their role in inducing regulatory macrophages to treat or prevent GvHD remains to be fully elucidated.…”
Section: The Potential Clinical Application Of Induced Tolerogenic Ma...mentioning
confidence: 90%
“…The current study by Lui et al 5 demonstrated that FRC macrophages induced ex vivo from BMC possesses the potential for immunosuppressive capacity and M-CSF was the critical cytokine for FRC to induce macrophages. 5 M-CSF was found to be highly expressed in FRC, but further study needs to define the accurate source of M-CSF at local stromal environment in lymph nodes including endothelial cells, follicular dendritic cells, marginal reticular cells, and fibroblastic FRCs. The ex vivo generation of tolerogenic macrophages may help ensure sufficient cells for the use of this therapy in the clinic.…”
Section: The Mechanisms Of Gvhd Attenuation Have Been Shown Directly ...mentioning
confidence: 99%
See 3 more Smart Citations